Reconfigurable beam pattern folded dipole antenna based on AMC structure - Lago, H. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper presents a reconfigurable beam direction folded dipole antenna with Artificial Magnetic Conductor (AMC). A coaxial probe placed in the middle of the proposed antenna as the medium to feed the current and then distributed to the radiating element. This research has the capability to steer the beam direction by implementing the radio frequency (RF) switch mechanism on the antenna. With a dimension of 24.5 mm × 54.5 mm, the antenna is potentially to sustain the gain and total efficiency of 6.4 dB and 90% respectively for all states at 9.41 GHz.